Epidemiological characteristics and influencing factors of fatal drowning in children under 5 years old in Hunan Province, China: case-control study - Zhiyu Liu; Fanjuan Kong; Lei Yin; Aihua Wang; Lili Xiong; Donghua Xie; Lizhang Chen; Xiaoqi Sheng (BMC, 2019)
Abstract Background Drowning is still the primary cause of death in children under 5 years old, however, little is known about the drowning of Hunan province children. This study identifies the previously unpublished incidence and characteristics of fatal drowning in children of Hunan Province, and provide a basis for formulating strategies for children's survival, development and protection. Methods Data were collected through sampling with the multistage stratified cluster. The case group included all fatal frowning children under 5 years old in 13 districts between October 2015 and September 2016. The control group was matched 1:1.The epidemic features and influencing factors of fatal drowning were analyzed retrospectively according to descriptive analysis, conditional univariate and multivariate logistic regression analysis. Results For children aged 0-4 years, the fatal drowning was 16.1/100000 in Hunan Province. Drowning rates were higher for boys than girls. The proportion of rural areas is much higher than that of urban areas. The 1-2 years age-group was the highest of all age groups. Fatal drowning mainly occurred in summer. The three leading drowning locations were pond, ditch and well. Playing close to the water were the leading activities that preceded fatal drowning. Multivariate logistic regression analysis showed that: children with primary caregiver education in high school and above (OR = 0.05) have a lower risk of fatal drowning; children with full-time care (OR = 0.17) have a lower risk; children who received unintentional drowning safety education (OR = 0.23) have a lower risk of fatal drowning. Children who were always swimming or playing near the water in the past 6 months (OR = 3.13) have a higher risk of fatal drowning. Conclusion The fatal drowning among children under 5 years is the result of the interaction of multiple factors. A significant number of child deaths could have been prevented if parents and other close relatives had been more concerned about the safety of their children. We should develop health education plans for villagers to warn them of the dangers of drowning and preventive measures.